1977
DOI: 10.1007/bf02166803
|View full text |Cite
|
Sign up to set email alerts
|

Eddy exchange coefficients in numerical models of the planetary boundary layer

Abstract: Abstract. Specification of the eddy exchange coefficients is perhaps one of the most difficult problems in the numerical modeling of the planetary boundary layer. These coefficients have been computc::d from finite-difference analogs 10 analytical expressions associated with surface boundary-layer similarity theory, which is based on observations in an equilibrium surface layer. This procedure leads to erroneous results in the region above the surface layer and in a non-equilibrium surface layer. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This might lead to erroneously turbulent mixing (Shir and Bornstein 1977;Walters et al 2007). Our proposal [Eq.…”
Section: Discussionmentioning
confidence: 99%
“…This might lead to erroneously turbulent mixing (Shir and Bornstein 1977;Walters et al 2007). Our proposal [Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 6 Vertical profiles at 1800 (solid lines) and 2400 (dashed lines) LST of: (a) modeled eddy diffusivity for momentum (K M ) and (b) horizontal wind speed (V) and perturbation potential temperature (θ'); from Shir and Bornstein (1977) The explanation for the K-minimum is thus: as Ri grows towards 1/α at the LLJ nose, 1-αRi decreases, then (ϕ m) −2 in (3) increases, and finally K decreases. Peak (and not minimum) K-values derived from turbulent flux measurements were, however, observed near LLJ peaks within the elevated west-coast subsidence inversion by Lile (1970).…”
Section: First Order Closuresmentioning
confidence: 99%
“…Also shown is the shape of the resulting equilibrium (EBL) and internal (IBL) boundary layers. See text for explanation of regions a-d; from Shir and Bornstein (1977) Results from the 2-D TKE model of SB77 showed that K(z) profiles in a neutral-stability flow in the equilibrium (i.e., equal sources and sinks of TKE) regions (a) and (d) of Fig. 9 depend only on z' 0 and z 0 , respectively.…”
Section: First Order Closuresmentioning
confidence: 99%
“…Examples of mechanistic models include IFUSE (Desai 2010), Ecosystem Demography (ED) (Moorcroft et al 2001), BIOME-BGC (Running and Coughlan 1988;Running and Gower 1991), Equilibrium Boundary Layers (EBL) (Shir and Bornstein 1977), Carbon Tracker (CT) (http://carbontracker.noaa.gov), HYBRID (White et al 1999), ECOSYS (Grant et al 2012), CEN-TURY (Glimanov et al 1997), LINKAGE (Post and Pastor 1996), etc. Most models use photosynthetically active radiation, vegetation index, atmospheric CO 2 concentration, air and soil temperatures, vapor pressure deficit, and soil moisture as inputs (Chen et al 2011;Sims et al 2008;Schubert et al 2012;Li et al 2007;Turner et al 2006).…”
Section: Introductionmentioning
confidence: 99%